Dalpiciclib in advanced breast cancer: introducing CDK4/6 inhibitors as a first-line treatment might not be the best strategy - Hindié, Elif (The lancet oncology, 2023)
In the phase 3 trial DAWNA-2, reported by Pin Zhang and colleagues,1 the CDK4/6 inhibitor dalpiciclib was investigated at 42 hospitals in China as a first-line treatment in combination with endocrine therapy (letrozole or anastrozole) in patients with hormone receptor-positive, HER2-negative advanced breast cancer. The primary endpoint of progression-free survival was met, with a median PFS of 30·6 months (95% CI 30·6–not reached) in the dalpiciclib group versus 18·2 months (16·5–22·5) in the placebo plus endocrine therapy group (stratified hazard ratio [HR] 0·51 [95% CI 0·38–0·69]; one-sided log-rank p<0·0001).1 In a previous trial, DAWNA-1, dalpiciclib showed efficacy in combination with fulvestrant in patients progressing after first-line endocrine therapy (median progression-free survival 15·7 months vs 7·2 months with placebo plus fulvestrant; HR 0·42, p<0·0001).2 The first-line use of this treatment means a longer exposure to the side-effects of CDK4/6 inhibitors. [...]DAWNA-2 also cannot inform optimal sequencing, because a crossover for patients in the placebo group to the dalpiciclib group after disease progression was not allowed.1 Findings reported in 2023 from SONIA, a nationwide phase 3 trial from the Netherlands, challenged the current sequencing strategies for CDK4/6 inhibitors for patients with hormone receptor-positive, HER2-negative advanced breast cancer.5 This trial showed that introducing CDK4/6 inhibitors in first-line treatment did not improve time from random assignment to second progression, overall survival, or quality of life, but increased the total duration of exposure to CDK4/6 inhibitors (by 16 months), the number of grade 3 or higher adverse events, and costs when compared with second-line use.5 Therefore, unless a risk of rapid progression exists, it is better to postpone the use of CDK4/6 inhibitors until the second line of endocrine therapy.